Pengembangan, Implementasi dan Pembuatan Perangkat Asesmen Berbasis Kelas untuk Pembelajaran Mata Kuliah Sistem Pemindah Tenaga - S Wakhinuddin (Jurnal Pendidikan dan Kebudayaan, 2011)
The research aims to develop, implement, and make a classroom-based assessment tools that validity, practice, and effectiveness to assess understanding of concepts, problem-solving skills, reasoning, communication, and connection of students, in learning Power train in the Department of Automotive Engineering FT UNP Padang. Assessment device designed to support the implementation of assessment in the majors, according to the demands of the curriculum. Based on these results a prototype device designed classroom-based assessment. The research method used is a combination of research and experimental development. This is research Experimental design of treatment methods used by design. In these experiments the samples selected at random classes and students. In the experimental class used classroom-based assessment tools, while the control class performed a written test. Research data were collected through classroom observation, interviews with faculty and students, as well as tests. The results of the research found that the student assessment based on class higher grade than the student group with a paper and pencil evaluate. This method is effective in increasing the understanding of concepts, communication skills, reasoning and problem solving students.